AB0771 IMPROVEMENT IN MORNING STIFFNESS IN SUBJECTS WITH PSORIATIC ARTHRITIS IS ASSOCIATED WITH IMPROVEMENTS IN PAIN, PHYSICAL FUNCTION AND PATIENT GLOBAL RESPONSE TO TREATMENT. (June 2019) - Orbai, Ana-Maria; Walsh, Jessica a.; Nash, Peter; Teng, Lichen; Guerette, Benoit; Alten, Rieke
Abstract : Background: Stiffness is an important component of inflammatory arthritis and plays a role in psoriatic arthritis (PsA) flare. Patients with inflammatory arthritis report difficulty with activities, "slowing down" due to stiffness and reduced quality of life. Stiffness is hard to quantify because it cannot be measured directly. Objectives: We examined morning stiffness in PsA patients treated with apremilast (APR) for 16 weeks in the aCTIVE study and explored the relationship between improvements in morning stiffness and pain, physical function and Patient's Global assessment of Disease activity (PtGA). Methods: Subjects who met CASPAR criteria for PsA, were biologic-naïve and had prior exposure to ≤1 conventional disease-modifying anti-rheumatic drug (DMARD) were randomized (1:1) to aPR 30 mg twice daily or placebo (PBO) for 24 weeks. Subjects initially randomized to PBO were switched to aPR at Week 16 (early escape) or Week 24. Duration of morning stiffness and severity, assessed by subjects' reported categories of stiffness (none, mild, moderate, moderately severe, severe), was reported. In the post hoc analysis, changes in morning stiffness severity and effect on pain, physical function and PtGA from baseline to Week 16 were compared between treatment arms. An analysis of covariance model adjusting the baseline value was used in the analysis, where missing values were imputed using the last-observation-carried-forward approach. Results: A total of 219 subjects were randomized (APR: n=110; PBO: n=109), and 192 remained in the study through Week 16. APR and PBO groups were balanced with respect to baseline tender joint count (mean [SD]: 17 [13] vs. 18 [14]), swollen joint count (mean [SD]: 9 [5] vs. 10 [6]), and severity of morning stiffness (moderate to very severe: 87% vs. 80%), as well as previous use of DMARD (67% vs. 72%), baseline use of non-steroidal anti-inflammatory drug (69% vs. 68%) and oral corticosteroid use (12% vs. 13%). Mean [SD] duration of morning stiffness at baseline was shorter with aPR vs. PBO (48 [49] vs. 72 [127] minutes). Baseline PtGA (mean [SD]: 5.9 [2.1] vs. 6.1 [2.0]), Patient's Pain Numeric Rating Scale (NRS; mean [SD]: 6.1 [1.9] vs. 5.8 [2.2]), Health assessment Questionnaire-Disability index (HAQ-DI; mean [SD]: 1.3 (0.6) vs. 1.2 [0.6]), Short-Form Health Survey version 2 (SF-36v2) Physical Component Summary (mean [SD]: 32.4 [9.2] vs. 33.9 [8.3]), SF-36v2 Physical Functioning subscale (mean [SD]: 33.2 [11.2] vs. 34.2 [10.1]) and SF-36v2 Bodily Pain domain (mean [SD]: 35.4 [7.6] vs. 37.4 [7.8]) scores were similar in the aPR and PBO groups, respectively. As early as Week 2, a significantly greater proportion of aPR vs. PBO subjects experienced morning stiffness severity improvements (≥1 category improvement) (43% vs. 21%; P =0.0007). Significant improvements in morning stiffness severity were sustained through Week 16 in aPR vs. PBO subjects (46% vs. 26%; P = 0.0015). Subjects with improvements in morning stiffness severity in the aPR and PBO groups showed consistent improvements in pain, physical function and PtGA at Week 16 (Table). In patients with unchanged stiffness severity, greater improvements were observed across outcome measures in the aPR vs. PBO group, although the change from baseline was less than the improved stiffness group. Worsened morning stiffness was associated with lack of improvement in other patient-reported outcome measures. Conclusion: In biologic-naïve PsA subjects treated with aPR for 16 weeks, improvement in morning stiffness severity was evident as early as Week 2 and associated with improvements in pain, physical function and PtGA response. Disclosure of interests: Ana-Maria Orbai Grant/research support from: abbVie, Celgene, Horizon Pharma, Janssen, Lilly, and Novartis, Consultant for: Lilly, Janssen, Novartis, Pfizer, and UCB, Jessica a. Walsh Grant/research support from: abbvie, Pfizer, Consultant for: abbvie, Celgene, Lilly, Novartis, Peter Nash Grant/research support from: abbVie, Bristol-Myers Squibb, Eli Lilly, Janssen, Novartis, Pfizer inc, Roche, Sanofi, UCB, Consultant for: abbVie, Bristol-Myers Squibb, Eli Lilly, Janssen, Novartis, Pfizer inc, Roche, Sanofi, UCB, Speakers bureau: abbVie, Bristol-Myers Squibb, Eli Lilly, Janssen, Novartis, Pfizer inc, Roche, Sanofi, UCB, Lichen Teng Employee of: Celgene Corporation, Benoit Guerette Employee of: Celgene Corporation, Rieke alten Grant/research support from: Bristol-Myers Squibb, Speakers bureau: Bristol-Myers Squibb